Current State: The Development of Thin Film Solar Cells Based on Kesteritee Compound - Fianti Fianti; Badrul Munir; Kyoo Ho Kim; Mohammad Ikhlasul Amal (Journal of Natural Sciences and Mathematics Research, 2016)
Thin film solar cell experience fast development, especially for thin film solar cell CdTe and Cu(In,Ga)Se2 (CIGS). However, the usage of rare element in the nature such as In, Te, and Ga and toxic such as Cd give limitation in the future development and production growth in big scale. Development of other alternative compound with maintain the profit of electronic and optic character which get from CIGS chalcopyrite compound will be explain. Compound of Cu2ZnSnSe4 (CZTSe) is downward compound from CIGS with substitute the In and Ga element with Zn and Sn. The compound kesterite structure can be modified with variation of chalcogen element to get wanted character in solar cell application. Efficiency record of photovoltaic devices conversion used this compound or downward reach 9.7%.©2016 JNSMR UIN Walisongo. All rights reserved.